Effect of heavy metals on epididymal morphology and function: An integrative review. (March 2022) - Machado-Neves, Mariana
Abstract: Male fertility has deteriorated over the last decades, and environmental risk factors are among the possible causes of this phenomenon. Pollutants such as heavy metals might accumulate in male reproductive organs to levels that are associated with reproductive disorders. Several studies reported detrimental effects of inorganic arsenic (iAs +3 /iAs +5 ), cadmium (Cd +2 ), lead (Pb +2 ), and mercury (Hg +2 /CH3 Hg +2 ) on the epididymis, which plays a crucial role in sperm maturation. However, the magnitude of their effects and the consequences on the physiology of the epididymis are still unclear. Therefore, an integrative review with meta-analyses was conducted examining 138 studies to determine how exposure to arsenic, cadmium, lead, and mercury affects epididymal morphology and functions, using primarily murine data from experimental studies as a source. This study showed that exposure to metal(loids) reduced epididymal weight, sperm motility, and sperm number. Inorganic arsenic, cadmium, and lead damaged sperm structures within the epididymal duct. While sodium arsenite, sodium arsenate, and lead acetate generate oxidative stress by an imbalance between ROS production and scavenging, cadmium chloride causes an increase in the pH level of the luminal fluid (from 6.5 to 7.37) that diminishes sperm viability. Inorganic arsenic induced a delay in the sperm transit time by modulating noradrenaline and dopamine secretion. Subacute exposure to heavy metals at concentrations < 0.1 mg L - 1 initiates a dyshomeostasis of calcium, copper, iron, and zinc that disturbs sperm parameters and reduces epididymal weight. These alterations worsen with prolonged exposure time and higher doses. Most studies evaluated the effects of concentrations > 1.1 mg L - 1 of heavy metals on the epididymis rather than doses with relevant importance for human health risk. This meta-analytical study faced limitations regarding a deeper analysis of epididymis physiology. Hence, several recommendations for future investigations are provided. This review creates a baseline for the comprehension of epididymal toxicology. Graphical abstract: Image 1 Highlights: The meta-analysis evidenced that the epididymis is sensitive to heavy metal poisoning. Heavy metals reduced epididymal weight, sperm motility, and sperm number. iAs and Pb +2 damaged sperm structure within the epididymis by ROS overproduction. Cd +2 creates an alkaline luminal fluid that diminishes sperm viability. This review highlighted several issues for exploration in future investigations.